СУДОВО-ПСИХОЛОГІЧНА ЕКСПЕРТИЗА В ЮРИСДИКЦІЙНОМУ ПРОЦЕСІ - Кощинець, Віктор Васильович (SUPREMANCE OF LAW, 2019)
The article draws attention to the fact that forensic psychological examination is one of the leading forms of the use of special psychological knowledge. It is analyzed the question of object and subject of forensic psychological research and indicated on the historical stages of its formation. Also, the author analyzes the problematic issues regarding the subject of this type of expertise and the need to develop the latest methods of their application.